Effect of Lifestyle Modification to Control the Blood Pressure in Hypertensive Individuals of Morang District, Nepal (Purbanchal University Health Journal, 2024)
Introduction: Hypertension is a strong, independent and etiologically relevant risk factor for cardiovascular diseases and therefore, the leading cause of preventable death worldwide. The purpose of this study was to determine the effect of multifaceted lifestyle modification intervention on blood pressure among hypertensive patients.Method: A quasi-experimental study was conducted among 67 participants in the medical Out Patient Department (OPD) of Purbanchal University Teaching Hospital. Participants were recruited through simple random sampling. The multifaceted intervention under investigation includes motivational interviews and 60-minute training sessions on dietary patterns and exercise, followed by 4 phone call follow-ups. Blood Pressure (BP) was measured both before and after the intervention, and the changes in BP were compared.Result: The study population comprised 67 adults with a mean age of 59.17 ± 12.63 years, where 61.2% were male. Following the intervention, a statistically significant reduction in blood pressure was observed. The mean systolic blood pressure decreased by 7.65 ± 4.45 mmHg, and the mean diastolic blood pressure decreased by 5.74 ± 4.45 mmHg (p < 0.005).Conclusion: The multifaceted lifestyle intervention resulted in a significant decrease in systolic and diastolic blood pressure. Thus, the use of this method as a supplementary treatment is recommended during visit to medical OPD.